DNA methylome and transcriptome changes caused by glucocorticoid treatment in T- cell acute lymphoblastic leukemia cells - Joshi, Shreya (My University, 2021)
Leukemia is a type of blood cancer and one of the most common pediatric cancers. T cell acute lymphoblastic leukemia (T-ALL) accounts for nearly 10-15 % and among pediatric patients. Chemotherapy is widely used to treat this cancer. The first line treatment of chemotherapy is induction phase where the glucocorticoids are used as chemotherapeutic drugs. DNA methylation changes can be associated with the cancer progression. Glucocorticoid binds to a glucocorticoid receptor and regulates the transcriptional activities. This can result in the upregulation or downregulation of the gene expression. The objective of this study is to understand the DNA methylation and transcriptome changes that are caused by glucocorticoid treatment in T-ALL cells. To achieve this objective, CCRF-CEM, a T lymphoblastoid cell line was used. The cells were treated with dexamethasone for 48 hours and 72 hours. RRBS libraries were prepared and the sequencing data was analysed using DNA methylome analysis pipeline. RNA sequencing data was analysed to study the gene expression changes. The functional enrichment of the gene ontologies and pathways was studied for these differentially expressed genes. DNA methylation status of the glucocorticoid receptor was studied by targeted bisulfite pyrosequencing. There were 28,395 genes present at both the time points. Statistically filtered gene list resulted into 538 upregulated and 2119 downregulated genes for 48 hours treatment. Whereas 1669 upregulated genes and 3290 downregulated genes for 72 hours treatment. Based on functional over-representation analysis the genes were enriched in several molecular functions, biological process and cellular components. The DNA methylation status of NR3C1 showed 1% methylation in majority of the sites showing response to dexamethasone treatment. The treatment does not cause epigenetic silencing of the NR3C1 gene through DNA methylation. This indicates that the cells were not resistant to the glucocorticoid treatment. DNA methylome analysis was done using bioinformatics tools and pipelines. However, the MspI enzyme digestion was not successful as the kit is yet to be optimized. Hence, the RRBS data was not sufficiently reliable.
Keywords: T- cell acute lymphoblastic leukemia, dexamethasone, DNA methylation, differential gene expression